PENGARUH PERCEIVED ORGANIZATIONAL SUPPORT DAN ORGANIZATIONAL EMPOWERMENT TERHADAP EMPLOYEE WELL-BEING DAN EMPLOYEE ENGAGEMENT - Hilfina, Hilfina; Putra, Made Surya (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.05.TAHUN.2023DO - 10.24843/EEB.2023.v12.i05.p14, 2023)
The purpose of the study was to analyze the effect of Perceived Organizational Support and Organizational Empowerment on Employee Well-Being and Employee Engagement and to analyze the effect of Employee Engagement on Employee Well-Being. Associative research conducted at PT. Danamas Insan Kreasi Andalan (DIKA) Denpasar Branch involved 160 respondents with the method of determining the sample using simple random sampling technique. Data were collected by questionnaire, and analyzed by descriptive analysis, PLS-based structural equation modeling (SEM) analysis. Research proves that Perceived Organizational Support has a positive and significant effect on Employee Well-Being, Perceived Organizational Support has a positive and significant effect on Employee Engagement, Organizational Empowerment has a positive and significant impact on Employee Well-Being, Organizational Empowerment has a positive and significant impact on Employee Engagement, and Employee Engagement has a positive and significant effect on Employee Well-Being. The results of this study have been able to clarify that Social Exchange has been confirmed in this study because this study reveals that Social Exchange Theory in the context of employee behavior in the work environment.